LITERATURE REVIEW : Hubungan Durasi Lama Duduk Terhadap Strength Lower and Upper Extremity Pada Lansia - Derio Fakhri Putra, (2020)
Physical activity that is often done by most people from young to adults is sitting because of sedentary lifestyle habits. Every human has a duration of sitting that varies depending on age and daily activities he does, too long sitting will cause weakness in the muscle strength of the upper and lower extremities. Usually this is experienced by parents who have reached the age of 60 years and over, because the functional muscles will decrease. This study was conducted to determine whether there is a relationship between sitting duration and the strength of the lower and upper extremities in the elderly. This research method is Literature Review by collecting various sources of literature. The parameters used to measure the duration of sitting using the EQ-5D-Y questionnaire, Accelerometer, ActivPAL3TM, Data from 45 and up study, and Measure of older adult sedentary time questionnaire to find out how long the elderly spend time to sit. Measurement parameters of muscle strength use Arm curl test 30s, Stand chair test 30s, Kes test using lord's strap.And analyze the results that have been obtained and then the relationship between the duration of sitting with muscle strength.